IMPACT OF HLA-DPB1 INCOMPATIBILITY ON THE RESULTS OF ALLOGENEIC HEMATOPOIETIC STEM CELLS TRANSPLANTATION FROM HLA-A-B-C–DRB1-DQB1-COMPATIBLE UNRELATED DONOR - E. G. Khamaganova; Е. N. Parovichnikova; L. A. Kuzmina; S. М. Kulikov; E. Р. Kuzminova; R. S. Chapova; V. G. Savchenko (Онкогематология)
Introduction. An accepted fact in allogeneic hematopoietic stem cells transplantation (allo-HSCT) from unrelated donors is that matching for HLA genes is critical to ensure the best outcomes for patients. The current gold standard is an unrelated donor matched for 10/10 HLA alleles (HLA-A, -B, -C, -DRB1, -DQB1). In the HLA-mismatched setting graft-versus-host disease (GVHD) is increased, and overall survival becomes significantly worse. The importance of HLA-DPB1matching is more controversial.The aim of our study was to evaluate the impact of HLA-DPB1 mismatches on outcome of patients who underwent 10/10 HLA matched unrelated HSCT.Materials and methods. 49 patients treated with allo-HSCT in transplant center of National Research Center for Hematology from 10/10 HLA-matched unrelated donors were included in the study. High-resolution typing for HLA-DPB1 was done by PCR with sequence specific primers (SSP) using Olerup typing kits. HLA-DPB1 permissive/nonpermissive mismatches were examined according to TCE groups. Overall survival, event-free survival and survival without acute graft-versus-host disease were calculated by Kaplan–Meier method, and compared with log-rank test. Proportional hazard Cox models were used for multivariate analysis.Results. The 3-year overall survival after allo-HSCT was 68 %, event-free survival – 51 %, acute GVHD-free survival – 62 %. No significant impacts of HLA-DPB1 disparities on overall, event-free survival and probability of acute graft-versus-host disease were observed. Patients with nonpermissive HLA-DPB1-incompatible donors had a tendency to increased event-free survival. The factors significantly increasing risk of acute GVHD were peripheral blood grafts, advanced-stage disease and male gender of recipients.Conclusion. The factors associated with acute GVHD are peripheral blood grafts, advanced-stage disease and male sex of recipients. For more precise evaluation of impact of HLA-DPB1-incompatibility on results of allo-HSCT further investigations are needed.